2008
DOI: 10.1152/ajpregu.00152.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptomic response to acute hypertension in the nucleus tractus solitarius

Abstract: Baroreceptor afferents project to the cardiovascular region of the nucleus tractus solitarius (cvNTS), and their cvNTS target neurons may play a role in governing the sensitivity and operating range of the arterial baroreceptor reflex (baroreflexes). Recent studies have shown differential gene and protein expression in the cvNTS in response to changed arterial pressure. However, the extent of these responses is unknown. Therefore, we collected differential global gene expression data in a time series following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 72 publications
(104 reference statements)
1
22
0
Order By: Relevance
“…Additionally, to focus on the cardiovascular regulatory role of the DVC, we included the genes encoding members of the angiotensin II type I receptor signaling (AT1R) pathway. Hypertension is a common physiological consequence of alcohol withdrawal and the signaling cascade is similar to that of many other GPCRs which have also been shown to be affected by chronic alcohol and withdrawal (Sanna et al 2002, Lomazzi et al 2008, Khan et al 2008). In sum, the tested set includes genes implicated in previous global gene expression studies, focused experiments on the molecular effects of alcohol, as well as other functionally related genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, to focus on the cardiovascular regulatory role of the DVC, we included the genes encoding members of the angiotensin II type I receptor signaling (AT1R) pathway. Hypertension is a common physiological consequence of alcohol withdrawal and the signaling cascade is similar to that of many other GPCRs which have also been shown to be affected by chronic alcohol and withdrawal (Sanna et al 2002, Lomazzi et al 2008, Khan et al 2008). In sum, the tested set includes genes implicated in previous global gene expression studies, focused experiments on the molecular effects of alcohol, as well as other functionally related genes.…”
Section: Methodsmentioning
confidence: 99%
“…275μm transverse sections were made with a McIlwain Tissue Chopper (Gamshall, England) for DVC microdissection with size-matched micropunches (≤1.25mm; Stoelting, Wood Dale, IL), as previously reported (Khan et al 2008). Bilateral punches from one animal were treated as a single sample.…”
Section: Methodsmentioning
confidence: 99%
“…We examined the NTS phenotype in vivo in its native tissue context using microfluidic qPCR across several hundred NTS neurons (Supplemental Material and Methods). In these single neurons we assayed the expression of 96 key genes derived from a previous microarray study of the nucleus (Khan et al 2008). NTS neurons were identified by two cell markers signifying distinct inputs, FOS and tyrosine hydroxylase (TH) (Fig.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…We focused on potential target genes that are involved processes with known functional impact on development and maintenance of hypertension. We developed a list of 144 potential target transcripts that are associated with AT1R signaling through Pkc, CamkII, Mapk, and Pi3k pathways, immediate early genes (e.g., Fos, Egr1, Egr2, Egr3, Jun, Junb), and ion channels and transporters, guided by our previous studies (27,34,39,40,42,51,53,54), as well as genes relevant to inflammatory pathways shown to affect blood pressure regulation, including interleukins, chemokines, and leukotrienes (19,52,60). Several of these pathways are enriched in astrocytes (e.g., inflammatory processes) compared with neurons (e.g., ion channels) compared with endothelial cells (e.g., junctional proteins), whereas the transcriptional regulators and signaling pathways may be common to all cell types (38).…”
Section: Resultsmentioning
confidence: 99%
“…At the assigned time of death, rat was killed via rapid decapitation and brain stems were excised, placed into ice-cold artificial cerebral spinal fluid (ACSF: 10 mM HEPES, pH 7.4; 140 mM NaCl; 5 mM KCl; 1 mM MgCl 2; 1 mM CaCl2; 24 mM D-glucose), and secured with agarose for sectioning [4% UltraPure low-melting-point agarose (Invitrogen) in ACSF]. We made 275 mm transverse sections with a McElwain Tissue Chopper (Gamshall) DVC microdissection with size-matched micropunches (1.25 mm; Stoelting, Wood Dale, IL), as previously reported (27). Bilateral region punches from one animal were treated as a single sample.…”
Section: Methodsmentioning
confidence: 99%